Pengaruh Return on Asset, Total Asset Turnover, dan Debt To Equity Ratio Terhadap Prediksi Kondisi Financial Distress: pada Perusahaan Sub Sektor Telekomunikasi yang Terdaftar pada Bursa Efek Indonesia Tahun 2018-2024 - Nabila Fitri Firmansyah; Diah Febriyanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The goal of this research focuses on analyzing the correlation between several essential performance indicators, such as return on assets, Total Assets Turnover, and debt to equity ratios, with respect to projected financial distress. The research subjects are corporations operating in the telecommunications sub-sector listed on the IDX from 2018 to 2024. This research adopts a quantitative approach with a descriptive and verification orientation. The data specifications utilized are numerical/quantitative data referring to secondary data in the form of annual accounting documentation of telecommunications sub-sector corporations published in 2018 to 2024. The approach to sample selection method was implemented through a purposive sampling technique, which requires certain criteria. The analytical methodology applied to identify the influence between variables was through t-tests and f-tests. The t-test for ROA and DER of 0.000 <0.05 indicates that these variables have an influence on Financial Distress individually. The sig. value of TATO of 0.127 > 0.05 indicates that it has no influence individually. The findings of the f-test showed a sig. value of 0.000 > 0.05, and the calculated F value with the F table was 13.931> 3.245. Thus, the three independent variables, namely ROA, TATO, and DER, have a significant effect simultaneously.